Analisis Pertumbuhan Ekonomi Antarwilayah di Provinsi Riau; Pendekatan Regresi Data Panel - Muhammad Hidayat; Ranti Darwin; Muhammad Fikry Hadi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
This study aims to examine the effect of decentralization, expenditure, investment, labor and development inequality on the inter-regional economic growth in Riau Province. The type of this research is quantitative descriptive research using secondary data type. Data analysis technique used in this research is using Data Panel Regression by using application program Eviews 9.0. The results of this study indicate that the variable of tax decentralization does not have a significant and positive influence on economic growth among regions in Riau Province. Government expenditure, investment, and labor have a significant influence on economic growth among regions in Riau Province. In addition, there is no significant and significant development on the economic growth between regions in Riau Province.